The Relationship between Body Mass Index and Menstrual Cycle of Female Students in SMK Negeri 2 Gorontalo - Maimun Ihsan; Faralia Eka Yoshida; Elvie Febriani Dungga (Universitas Negeri Gorontalo, 2023)
Introduction: The menstrual cycle is a regularly coordinated hormonal process in a woman's body which can be an indicator to describe a woman's reproductive health. Riskesdas (2018) shows that 11.7% of Indonesian youth experience menstrual cycle disorders. Body Mass Index (BMI) can be a factor that can interfere with the menstrual cycle, so the purpose of this study was to analyze the relationship between Body Mass Index (BMI) and the menstrual cycle in female students at SMK Negeri 2 Gorontalo.Method: This study used a cross-sectional design. The sample was selected using a probability sampling technique utilizing simple random sampling with a total sample of 173 people, the instruments used were scales and meters for body mass index data and menstrual cycle questionnaires. The study was conducted in November 2022. The relationship between BMI and the menstrual cycle was tested using the Spearman correlation test.Results: Out of 173 respondents whose data were analyzed, 128 respondents (74%) had a normal BMI, 19 respondents (11%) were underweight, and 26 respondents (15%) were overweight. Among the total respondents, 117 (67.6%) had a normal menstrual cycle, while 56 (32.4%) had an abnormal cycle. There were 14 respondents (10.9%) with normal BMI, 18 respondents (94.7%) with underweight BMI, and 24 respondents (92.3%) with overweight BMI who had an abnormal menstrual cycle. There was a significant correlation between BMI and menstrual cycle among female students of SMK Negeri Gorontalo, with a p-value of 0.019.Conclusion: significant association exists between BMI and menstrual cycle among SMK Negeri 2 Gorontalo female students. This study can serve as a recommendation for the school to provide information regarding reproductive health, particularly menstrual cycles.